Ayurvedic Management Of Hepatorenal Syndrome: A Case Study - P, Anukrishna; S.N, Spoorthi; M.D, Beena; C.S, Saisudha.; R, Sharanya; M. Varma, Vishnu; Raghunath, Raghunath; Kumar B G, Chethan; K M, Anil Kumar (Journal of Neonatal Surgery, 2025)
Introduction: Hepatorenal Syndrome (HRS) is a serious complication of advanced liver disease characterized by functional renal failure without any structural kidney damage, typically occurring in patients with cirrhosis, severe liver failure or fulminant hepatic failure and marked by renal vasoconstriction and reduced renal perfusion. This article emphasizes the successful case study of Hepatorenal Syndrome which was treated at our hospital in a comprehensive manner both locally and systemically by utilizing the principles of Ayurveda in reducing the symptoms and thereby improving quality of the subject. Methodology : A 48 year old male patient diagnosed with Hepatorenal syndrome, presenting with complaints of Massive Ascites, Swelling in both lower limbs, reduced urine output, reduced appetite, reduced sleep, Generalized weakness and itching all over the body with elevated creatinine and bilirubin levels and low Haemoglobin count was administered with comprehensive Ayurvedic management which included Nithya Virechana, Ekanga Lepa over Abdomen, Basti and Shamanoushadhis followed by Pathya Ahara Sevana. Result : Marked improvements were observed in the patient's subjective symptoms, along with a reduction in creatinine and bilirubin levels and an increase in haemoglobin count. Discussion: By utilizing the principles of Ayurveda case of Hepatorenal syndrome was successfully managed at our hospital. The combined effect of external therapies and Shamanoushadhis facilitated effective liver detoxification, reduced fluid accumulation, improved appetite and sleep, alleviated generalized weakness, and significantly enhanced the patient’s overall well-being, thereby contributing to a better quality of life